Is abdominal obesity at baseline influencing weight changes in observational studies and during weight loss interventions?. Issue 5 (23rd November 2018) - Svendstrup, Mathilde; Allin, Kristine Højgaard; Ängquist, Lars; Schnohr, Peter; Jensen, Gorm Boje; Linneberg, Allan; Thuesen, Betina; Astrup, Arne; Saris, Wim H M; Vestergaard, Henrik; Sørensen, Thorkild I A
ABSTRACT: Background: Body fat distribution is a marker of metabolic health independent of body size. Visceral fat accumulation has been suggested to result from a decreased expandability of the subcutaneous fat depots. Furthermore, the visceral fat may be easier to mobilize than the peripheral fat. We examined whether differences in abdominal obesity at baseline influenced prospective body-weight changes. Objective: In this study we examined whether body-fat distribution at baseline was associated with long-term and short-term weight changes. Design: We included 3 observational studies ( n total = 7271) with mean follow-up times of 5–9 y and two 8–10-wk weight loss intervention studies ( n total = 1091). We examined the association between baseline waist circumference and weight changes in a substitution regression model, where body weight, height, and fat-free mass were fixed so that a difference in waist circumference would reflect a difference in body fat distribution alone. The results were summarized in meta-analyses. Results: In the observational studies, we found no associations between baseline waist circumference and subsequent weight change in men (β: 0.03 kg; 95% CI: −0.01, 0.08 kg; P = 0.19), but a negligible inverse association in women (β: −0.05 kg; 95% CI: −0.08, −0.01 kg; P = 0.01). There was no association between baseline waist circumference and weight loss in the intervention studies (men: β: −0.05 kg; 95% CI: −0.13, 0.03 kg; P = 0.25; women: β: −0.00 kg; 95% CI: −0.03, 0.03 kg; P = 0.84). However, in all studies, the SDs of the weight change residuals were greater, the greater the waist circumference at baseline. This trend was statistically significant in women in most studies as well as in men in 1 of the studies. Conclusions: With narrow CIs in 3 observational studies and 2 weight loss interventions, we did not find any clinically or epidemiologically relevant association between baseline abdominal obesity and weight change. However, the present study suggests that a greater baseline abdominal obesity is a marker for greater weight fluctuations. The CCHS trial was registered at www.clinicaltrials.gov as NCT02993172. The Health2006 trial was registered at www.clinicaltrials.gov as NCT00316667. The ORG study was conducted before trial registration was required. The NUGENOB trial was registered at www.isrctn.com as ISRCTN25867281. The DiOGenes trial was registered atwww.clinicaltrials.gov as NCT00390637.